Major and minor complications after anterior rectal resection for deeply infiltrating endometriosis - Renner, Stefan; Kessler, Hermann; Topal, Nalan; Proske, Kim; Adler, Werner; Burghaus, Stefanie; Haupt, Werner; Beckmann, Matthias; Lermann, Johannes (Archives of Gynecology and Obstetrics, 2017)
The aim of the present study was to analyze major and minor complications-including long-term impairment of intestinal, bladder, and sexual function-following surgery for deeply infiltrating endometriosis using anterior rectal resection.Patients who had undergone anterior rectal resection due to endometriosis between 2001 and 2011 were included (n = 113). Clinical and surgical data, as well as minor and major complications, were recorded. A questionnaire was sent to the patients and also to a healthy control group (n = 100).Major complications occurred in 15.9% of cases and minor complications in 15%. Patients with postoperative ileostomies (n = 8) initially had ultralow anastomoses significantly more often. The questionnaire response rate was 77%, with a mean follow-up period of 85.9 months. Weak urinary flow was reported by 22.4% of the patients: a feeling of residual urine by 18.4%; more than one bowel movement/day by 57.5%; and insufficient lubrication during intercourse by 36.5%. These results differed significantly from the control group. Subgroup analysis showed no statistical associations between questionnaire responses and major or minor complications, ultralow anastomoses, bilateral dissection of the sacrouterine ligaments, or dissection of the vagina and rectovaginal space.The major complication rate was consistent with the literature, but there were fewer minor complications. Patients with bowel anastomoses below 6 cm (ultralow) should receive information postoperatively about the high risk of insufficiency and should be closely monitored. The high rate of bladder, bowel, and sexual function impairment, and inadequate data make further prospective studies on this topic necessary.
EVALuna2:15312